Behavior of sexually transmitted infections in adolescents - Lidia Pérez Morffi; María de los Ángeles Santos Blanco; Yenisey de la Paz Pérez (Acta Médica del Centro, 2014)
Studies made at the global level in Cuba on sexually transmitted infections and acquired immunodeficiency syndrome in adolescence demonstrate the need for comprehensive care for all sectors of society to achieve physical, mental and social balance of teenager , which will help in their education, the only preventive  weapon against these diseases. Despite the known characteristics the incidence of the problems of sexual and reproductive health, including the increase of sexually transmitted infections and acquired immunodeficiency syndrome. Sexually transmitted infections in general, and especially the human immunodeficiency virus and acquired immunodeficiency syndrome in adolescents and young adults are a serious health problem and the risk of suffering is closely related to sexual behavior and ways protected, among other factors.